Simulation-Based Analysis of Packet Scheduling Strategies and Traffic Load Effects on Network QoS - Wirasapta, Andicho Haryus; Pamungkas, Tiara Deta; Mishi , Salmuna Sajjad (Energy Insights, 2026)
This study addresses a significant gap in quality of service (QoS) simulation research by evaluating the impact of packet scheduling mechanisms on network performance under varying traffic loads and link capacities. Using MATLAB simulations, we introduce a novel framework to assess the performance of FIFO, Priority Scheduling, and Weighted Round Robin (WRR) mechanisms in a network supporting voice, video, and data traffic. The results highlight that WRR provides the most balanced performance, achieving lower delay (59 ms), reduced jitter (11 ms), higher throughput (4.18 Mbps), and lower packet loss (3.2%) compared to FIFO and priority scheduling. This study fills a critical gap by offering new insights into QoS performance across heterogeneous network environments, with practical implications for optimizing network performance. Furthermore, the findings contribute to theoretical research by demonstrating the need for adaptive scheduling strategies in real-time communication networks, especially under high-traffic conditions.